Global Positioning System (GPS) guided mobile robot - Md Janis, Mohd Aizuddin (2013)
This thesis represents the design of GPS guided mobile robot using GPS Module EM406A and PIC18F4550. The scope of this project involves in both hardware and software development. The EM406A is used to provide localization and navigation of the mobile robot. The signal produced by EM406A is in RS-232 signal level, so serial communication must be used to communicate with the PIC18F4550. The data that is collected from the EM406A is compared and used to control the direction and Pulse Width Modulation (PWM) of the DC motor. This project development is started with literature review where all information and requirement regarding the project is collected. The requirements of the project are GPS Module EM406A, PIC18F4550, MAX232 and DC Motor.